Formation of Segregated and Integrated Groups - Alison Watts (Fondazione Eni Enrico Mattei (FEEM), 2006)
A model of group formation is presented where the number of groups is fixed and a person can only join a group if the groups members approve the persons joining. Agents have either local status preferences (each agent wants to be the highest status agent in his group) or global status preferences (each agent wants to join the highest status group that she can join). For both preference types, conditions are provided which guarantee the existence of a segregated stable partition where similar people are grouped together and conditions are provided which guarantee the existence of an integrated stable partition where dissimilar people are grouped together. Additionally, in a dynamic framework we show that if a new empty group is added to a segregated stable partition, then integration may occur.
Keywords: C7; D6; 330; Group Formation; Stable Partition; Segregation; Integration